2D spatially-resolved depth-section microfluidic flow velocimetry using dual beam OCT - Hallam, Jonathan M.; Rigas, Evangelos; Charrett, Thomas O. H.; Tatam, Ralph P. (MDPI, 2020)
A dual beam optical coherence tomography (OCT) instrument has been developed for flow measurement that offers advantages over microscope derived imaging techniques. It requires only a single optical access port, allows simultaneous imaging of the microfluidic channel, does not require fluorescent seed particles, and can provide a millimetre-deep depth-section velocity profile (as opposed to horizontal-section). The dual beam instrument performs rapid re-sampling of particle positions, allowing measurement of faster flows. In this paper, we develop the methods and processes necessary to make 2D quantitative measurements of the flow-velocity using dual beam OCT and present exemplar results in a microfluidic chip. A 2D reference measurement of the Poiseuille flow in a microfluidic channel is presented over a spanwise depth range of 700 μm and streamwise length of 1600 μm with a spatial resolution of 10 μm, at velocities up to 50 mm/s. A measurement of a more complex flow field is also demonstrated in a sloped microfluidic section.
Keywords: particle image velocimetry (PIV); flow measurement; microfluidics; interferometry; optical coherence tomography (OCT)